FOREIGN EXPERIENCES ON IMPROVEMENT OF QUARANTINE SERVICE IN PROMOTION OF EXPORT OF FRUIT AND VEGETABLE PRODUCTS AND POSSIBILITIES OF THEIR USE - Alimov Murodkosim Achilovich (American Journals, 2023)
When joining the WTO, the existing phytosanitary requirements in the Republic of Uzbekistan will have to be harmonized with the international phytosanitary requirements of this international organization. The State Plant Quarantine Inspectorate of the Republic of Uzbekistan must comply with the “Agreement on the Application of Sanitary and Phytosanitary Measures” introduced by the WTO organization. Phytosanitary requirements should have a "technical basis".
Keywords: World Trade Organization, harmful organism, Phytosanitary Risk Analysis, technical basis, foreign trade, regional organizations plant quarantine and protection, economic factors, WTO rules.